1988
DOI: 10.1126/science.2841762
|View full text |Cite
|
Sign up to set email alerts
|

NMDA Receptor Losses in Putamen from Patients with Huntington's Disease

Abstract: N-Methyl-D-aspartate (NMDA), phencyclidine (PCP), and quisqualate receptor binding were compared to benzodiazepine, gamma-aminobutyric acid (GABA), and muscarinic cholinergic receptor binding in the putamen and cerebral cortex of individuals with Huntington's disease (HD). NMDA receptor binding was reduced by 93 percent in putamen from HD brains compared to binding in normal brains. Quisqualate and PCP receptor binding were reduced by 67 percent, and the binding to other receptors was reduced by 55 percent or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
136
0
2

Year Published

1991
1991
2008
2008

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 376 publications
(142 citation statements)
references
References 41 publications
3
136
0
2
Order By: Relevance
“…These findings are in good accordance with human post-mortem studies (Glass et al 2000) that have been confirmed by in vivo PET studies, which clearly demonstrate a massive loss of D 2 dopamine (Turjanski et al 1995;Ginovart et al 1997;Antonini et al 1998;Araujo et al 2000;Pavese et al 2003) and A 2A adenosine (Ishiwata et al 2002) receptors, respectively. A reduction of NMDA receptor density, which has been described in the putamen of HD patients (Young et al 1988), could not be confirmed. Instead, we found a loss of NMDA receptor binding in the ventral striatum.…”
Section: Regional Pattern Of Receptor Changesmentioning
confidence: 68%
“…These findings are in good accordance with human post-mortem studies (Glass et al 2000) that have been confirmed by in vivo PET studies, which clearly demonstrate a massive loss of D 2 dopamine (Turjanski et al 1995;Ginovart et al 1997;Antonini et al 1998;Araujo et al 2000;Pavese et al 2003) and A 2A adenosine (Ishiwata et al 2002) receptors, respectively. A reduction of NMDA receptor density, which has been described in the putamen of HD patients (Young et al 1988), could not be confirmed. Instead, we found a loss of NMDA receptor binding in the ventral striatum.…”
Section: Regional Pattern Of Receptor Changesmentioning
confidence: 68%
“…Excitotoxicity has been implicated in the pathophysiology of various human brain disorders, including Alzheimer disease [9,10], Parkinson disease [11], Huntington disease [12], schizophrenia [13], and bipolar disorder [14][15][16]. Studies have demonstrated increased concentrations of glutamate and reduced levels of NMDA receptor (NR) subunits in the brain of some of these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Intrastriatal injection of glutamate or kainic acid in rat causes selective loss of medium spiny neurons that are also selectively affected in HD (15). In the brains of HD patients, NMDA receptor-binding sites were disproportionately reduced even at the pre-symptomatic stage (16,17). In neuronal cells expressing the mutated huntingtin or mice transgenic for HD, NMDA receptors are highly responsive to the receptor agonists, and the receptor-mediated current is also significantly increased (18 -20).…”
mentioning
confidence: 99%